Implementasi Metode RAD Untuk Pendaftaran Lowongan Kerja Melalui Bursa Kerja Berbasis Website - M Yoka Fathoni; Sena Wijayanto; Sandhy Fernandez; Toni Anwar; Yogo Dwi Prasetyo (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The system of recruiting workers in schools through special job fairs (BKK) is considered to be ineffective because the provision of job vacancies to alumni still uses information manually, such as using wall magazines as a place to post job vacancies and using social media such as Facebook as a means of information. Job opening is also considered less efficient due to limited users limited by social media itself. Registration is also done manually by alumni who come directly to BKK to register, and the vacancy data collection is still done manually, so it takes longer time to process registration data. The purpose of this research is to build a job vacancy registration system application through the BKK website based on the website to make it easier for BKK to provide job vacancy information and make it easier to recruit workers. This application development study uses the Rapid Application Development (RAD) method. Test the app using system black box and user usability testing methods.